1973
DOI: 10.1128/jb.116.2.972-980.1973
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Dimorphology and Respiration in Mucor genevensis Studied with Chloramphenicol

Abstract: Growth of Mucor genevensis , a facultatively anaerobic dimorphic mold, in high concentrations of chloramphenicol (4 mg/ml) leads to increased numbers of yeast-like cells and small club-like mycelial forms. This change in morphology is accompanied by a threefold increase in the mass doubling time, the loss of cyanide-sensitive respiration, and the development of cyanide-insensitive respiration. Associated with these changes is the absence of cytochromes aa 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

1974
1974
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 12 publications
2
12
0
Order By: Relevance
“…tion, and carbon dioxide evolution were very similar to those obtained for anaerobic cultures grown in the absence of the antibiotic ( Table 1). The low potential respiration and its almost complete insensitivity to cyanide indicated that an inhibition of normal mitochondrial biogenesis had occurred in support of results found with batch-grown cultures (10). However, the morphology of cells in these continuous cultures was almost completely mycelial and comparable with aerobic filamentous cultures grown in the Ĉ c ' X '…”
Section: Methodssupporting
confidence: 79%
See 1 more Smart Citation
“…tion, and carbon dioxide evolution were very similar to those obtained for anaerobic cultures grown in the absence of the antibiotic ( Table 1). The low potential respiration and its almost complete insensitivity to cyanide indicated that an inhibition of normal mitochondrial biogenesis had occurred in support of results found with batch-grown cultures (10). However, the morphology of cells in these continuous cultures was almost completely mycelial and comparable with aerobic filamentous cultures grown in the Ĉ c ' X '…”
Section: Methodssupporting
confidence: 79%
“…The latter alternative seems more likely, in view of the fact that under glucose-limited conditions chloramphenicol inhibits the development of functional oxidative capacity in the cells, but does not induce yeast-like morphology in continuous culture. The fact that yeast-like forms are promoted by chloramphenicol in batch cultures (10,28) is most probably due to the presence of higher glucose concentrations for most of the growth cycle.…”
Section: Methodsmentioning
confidence: 99%
“…i(18 THE JOURNAL OF CELL BIOLOGY -VOLUME 66,1975 the colonies derived from U. cynodontis hyphae, and the percentage of the altered colonies, on solid medium, varies with the glucose concentration in the growth medium. Similar modifications, on fungi, have been described in the literature: CAP promotes yeastlike morphology in Mucor genevensis (Clark-Walker, 1973); this change is accompanied by a loss of cyanide-sensitive respiration, the development of cyanide-insensitive respiration, and the modification of the mitochondrial membranes. A recent paper (Hanssens et al, 1974) described similar effects of CAP on Moniliella tomentosa.…”
Section: Reversible Phenotypic Changessupporting
confidence: 76%
“…The work of Clark-Walker (1973) is relevant to the present discussion: that author observes that CAP induces yeastlike morphology from the in 4% glucose complex medium with CAP 1,500 ug/ml. mycelial form in M. genevensis (a facultative anaerobe) and that the effect of CAP on this organism is reversed by 10% glucose; although CAP is shown to affect the mitochondria in this organism, that author suggests that CAP also inhibits glucose transport or glycolysis: thus, the effect of the drug on morphology cannot be precisely explained by an interference with mitochondrial function.…”
Section: Permanent and Long-lasting Effects Of Cap On Morphologymentioning
confidence: 95%
“…This resembles very strongly the change from the mycelial (M-) to the yeast (Y-) form in Mucorales and other fungi with dimorphic growth. Whereas formerly a conversion of the metabolism to glycolysis or an inhibition of respiration seemed to explain this effect sufficiently (CLARK-WALKER 1972, 1973, TERENZI and STORCK 1969, FRIEDENTHAL et al 1974, SCHULZ et al 1974, GARCIA and VILLA 1980, newer results demonstrate that the situation is more complicated. Anaerobiosis leads to the formation of the Y-form only if fermentable sugars are present (glucose > fructose > mannose > galactose), but not with maltose, succinate or glycerate (BARTNICKI-GARCIA 1968).…”
mentioning
confidence: 98%